ANALYSIS OF GROWTH AND YIELD OF SOYBEAN (Glycine max L. Merr.) IN RESPONSE TO LIQUID ORGANIC FERTILIZER AND NPK APPLICATION - Edi Wirman; Ermawati Ermawati; Anggi Julian Julian (Universitas Muhammadiyah Mataram, 2025)
Soybean is a strategic commodity in the national food system; however, its productivity remains low. The application of liquid organic fertilizer (LOF) and NPK fertilizer is considered an effort to improve soybean productivity. This study aimed to evaluate the effects of LOF and NPK fertilizer on the growth and yield of soybean. The research was conducted on dryland from April to July 2024 using a factorial Randomized Block Design with three replications. The first factor was LOF concentration (0, 25, and 50 mL L⁻¹), and the second factor was NPK rate (0, 150, and 300 kg ha⁻¹). Observed variables included plant height, number of primary branches, number of effective root nodules, number of filled pods, percentage of filled pods, percentage of empty pods, 100-seed weight, dry seed weight per plant, and dry seed weight per plot. Data were analyzed using analysis of variance followed by the Least Significant Difference (LSD) test at the 5% significance level. The results showed no significant interaction between LOF and NPK for all observed variables. Application of NPK at 150 kg ha⁻¹ was the optimal rate for increasing plant height, number of effective root nodules, and dry seed weight per plant, whereas LOF derived from Cladophora glomerata had no significant effect. Therefore, application of NPK at 150 kg ha⁻¹ is recommended to improve soybean productivity on dryland, and further studies are needed to evaluate the effectiveness of LOF under various soil conditions with reduced NPK rates.